Monitoring of dissolved ciguatoxin and maitotoxin using solid-phase adsorption toxin tracking devices: application to Gambierdiscus pacificus in culture - Caillaud, Amandine; de la Iglesia, Pablo; Barber, Esther; Eixarch, Helena; Mohammad Noor, Normawaty; Yasumoto, Takeshi; Dioge`ne, Jorge (Elsevier, 2011)
The suitability of solid phase toxin tracking (SPATT) for the detection of dissolved ciguatoxins (CTXs) and maitotoxins (MTXs) was evaluated under in vitro conditions for its possible application to toxin evaluation in Gambierdiscus spp. cultures and in the field. Pacific type 1 CTX (CTX1B) and MTX standards tracked by the DIAON1 HP20 resin were evaluated using two Neuroblastoma cell based-assays (Neuro- 2a CBA) specifically conceived for these two toxins. Recoveries were estimated at 90.9 (6.4), 85.5 (13.2) and 89 (11.3)% for dissolved CTX1B after respectively 24, 72 and 120-h exposure, and 66.2 (11.9)% for dissolved MTX after 72-h exposure. The approach was further applied for the detection of dissolved toxins in the culture medium of Gambierdiscus pacificus with tentative confirmation of the identity of CTXs congeners using liquid chromatography–tandem mass spectrometry (LC–MS/MS) analysis. Both the Neuro-2a CBA for CTXs and LC–MS/MS analysis allowed the identification and quantification of dissolved CTX-like compounds from day 16 to 47 of the culture, being the congeners 51-hydroxyCTX-3 C and 2,3-dihydroxyCTX- 3C determined as the most abundant by LC–MS/MS. The MTX-like toxicity was detected from day 19 to 47 (final of exponential to decade growth phases). Dissolved CTX- and MTX-like toxicity evaluated with SPATT devices and intracellular CTX- and MTX-like toxicity evaluated in harvested G. pacificus cells from culture were analyzed to investigate possible physiological variations of toxin production between the different growth phases of G. pacificus cultures. These results confirmed for the first time the suitability of SPATT devices for recovering dissolved CTX1B and MTX under in vitro conditions. The use of SPATT devices may be considered as a useful approach to monitor the incidence and prevalence of CTX in ciguatera endemic areas,as well as to increase the knowledge on CTX- and MTX-producing species.